Entrepreneurial Masculinity: A Fatherhood Perspective - Hytti Ulla; Karhunen Päivi; Radu-Lefebvre Miruna (Sage, 2025)
This article investigates how fatherhood (or the prospect thereof) shapes entrepreneurial masculinities. Drawing on constructivist grounded theory, we analyze 22 life story interviews with Finnish men technology founders and identify three entrepreneurial masculinities enacted by men to accommodate concurrent normative ideals at the intersection of work and family life. These entrepreneurial masculinities alternatively maintain, restructure, and resist entrepreneurial and parental hegemonic masculinities and are subject to generational and situational scripts. We contribute to the gender and entrepreneurship literature by revealing that the neoliberal new father discourse blurs hegemonic masculinities leading entrepreneurial masculinities to emerge as hybrid hegemonic masculinities.